2006
DOI: 10.2105/ajph.2004.057422
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Influences on the Use of Health Facilities for Childbirth in Africa

Abstract: Studies of maternal health seeking behaviour have focused on individual and household level factors. This analysis examines community level influences on the decision to deliver a child in a health facility across six African countries.Demographic and Health Survey data are linked with contextual data, and multilevel models are fitted to identify the determinants of childbirth in a health facility in the six countries. There are strong community level influences on a woman's decision to deliver her child in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
211
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(242 citation statements)
references
References 37 publications
24
211
4
3
Order By: Relevance
“…These results are consistent with findings elsewhere examining the use of maternal health facilities (Stephenson et al, 2006;Ahmed et al, 2010) and underline the importance of women's empowerment within the household, allowing them to have greater decision-making powers regarding both their own health and that of their children.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with findings elsewhere examining the use of maternal health facilities (Stephenson et al, 2006;Ahmed et al, 2010) and underline the importance of women's empowerment within the household, allowing them to have greater decision-making powers regarding both their own health and that of their children.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in rural India, traditional pregnancy is considered to be a natural state of being. These beliefs, coupled with mis-conceptions and fears of medical institutions, have led women to continue to rely on home births in India (Stephenson, Baschieri, Clements et al, 2006). As a result, rural women may continue to under-utilize health care facilities relative to urban women despite the introduction of free maternal care schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature (Babalola and Fatusi, 2009;Baru et al, 2010;Stephenson et al, 2006;Thind et al, 2008), this study included the following socioeconomic and demographic factors: region (central, north, east, northeast, west, or south), place of residence (rural or urban), religion of the head of the household (Hindu, Muslim, or others), caste of the head of the household (scheduled tribe, scheduled caste, or others), wealth index for the household (poorest, poor, middle, rich or richest), educational status of women and their partners (illiterate, literate but below primary school, primary school completed but below middle school, middle school completed but below high school, or high school or above), loss of a child (no child lost or at least one child lost), sex composition of children (no son and no daughter, number of sons greater than daughters, number of sons less than daughters, or equal sons and daughters), ever having pregnancy terminated (no or yes), child's age in months (0-23, 24-35, 36-47, or 48-59), and birth order (second order birth, first order, third order, or 3+ order). The first category of each of these independent variables is considered as the reference category in the multivariate analyses.…”
Section: Measurementsmentioning
confidence: 99%
“…While the community-based health planning and services (CHPS) strategy introduced through the Ghana health service (GHS) provides a platform to deploy health services in rural areas, there are still a number of social norms, and cultural practices at the community level that influence maternal health-seeking behavior including beliefs that husbands are not responsible for supporting their pregnant wives to maintain their antenatal schedules by providing finance, transport, or company (Nyonator, 2005; Sumankuuro, Crockett, & Wang, 2017). Several studies have shown that community beliefs and attitudes influence a woman’s decision to seek care (Kruk, Rockers, Mbaruku, Paczkowski, & Galea, 2010; Stephenson, Baschieri, Clements, Hennink, & Madise, 2006). Previous research in Ghana has found that women who live in communities where more women perceive higher use of facility delivery are more likely to deliver in a facility (Speizer, Story, & Singh, 2014).…”
Section: Introductionmentioning
confidence: 99%